Stroke Impact Scale Version 2: Validation of the French Version. Issue 5 (1st May 2015) - Caël, Sylvia; Decavel, Pierre; Binquet, Christine; Benaim, Charles; Puyraveau, Marc; Chotard, Morgane; Moulin, Thierry; Parratte, Bernard; Bejot, Yannick; Mercier, Mariette
Abstract : Background: Almost 1 person in 1, 000 experiences a stroke annually in France. Health-related quality-of-life (HRQoL) measurement with specific questionnaires is useful to study the consequences of stroke on patients' daily lives. Objective: The purpose of this study was to validate the French version of the Stroke Impact Scale (SIS) questionnaire, as no disease-specific questionnaire was validated in French heretofore. Methods: Two hundred eighty-eight patients with stroke were classified into 2 groups (158 acute, 130 chronic). Rate of item completion, test-retest reliability, sensitivity to change, and construct validity, convergent validity, and discriminant validity of the questionnaire were assessed. Acute group patients were recruited during the first month poststroke and followed for 3 months. Chronic group patients (stroke dating from 1 year) were recruited from outpatient consultations. The first 100 patients in the chronic group were called back 15 days after inclusion for test-retest measurements. The Barthel Index, Hospital Anxiety and Depression Scale (HADS), and Duke Health Profile questionnaires were administered. Results: The French version of the SIS was well accepted by all participants. It had good reproducibility. Cronbach alpha was 89% for all scales. A ceiling effect was noted in the majority of scales. Physical domains were significantly correlated to other measures of physical capacity (Barthel Index and Duke Health Profile; Spearman coefficients were between .5 and .73), and the emotional and social domains were significantly correlated to almost all domains of the Duke Health Profile. Psychometric properties were similar to those of the US version. Responsiveness was good for physical and emotional domains. Limitations: Validation was conducted only on people who were able to answer the questionnaire. Conclusions: The French SIS version presents good psychometric properties, except for ceiling effect. This is the first stroke-specific questionnaire evaluating perceived health after stroke to be validated in France and could be useful for further investigations of HRQoL after stroke.